Denture impaction in the oesophagus: correlation of site and duration of impaction with sequelae (2019)
Background: Denture restores aesthesis and function of missing teeth. Accidentally swallowed denture is an otorhinolaryngology emergency. The types of denture base and oesophageal anatomy influence the site of impaction. Objective: To review site of denture impaction and factors associated with site of impaction. To correlate site and duration of denture impaction before removal with associated sequelae. Method: A retrospective study of 27 patients managed in Otorhinolaryngology Department of University College Hospital Ibadan, Nigeria for oesophageal partial denture impaction, between August 2006 and September 2016. The demographic and clinical data of the patients were extracted from the hospital records, and statistical tables were used to illustrate the data. Results: A total of 27 patients; 14(51.9%) males and 13(48.1%) females, (M: F, 1.1:1) were studied. The age ranged from 24 to 77 years (mean age 49.0 ± 14.2years). Dentures were worn for 3 to 30 years (mean 3.8 ± 2.3years) without follow-up visit to dentist and 85.2% were upper dentures. All patients had history of accidental ingestion of denture, and the mean site of impaction was 18.2 ± 3.2cm from upper incisor, typically at upper cervical oesophagus in elderly patients and in lower oesophagus in females. There was no association between site of denture impaction, duration of denture impaction and operative findings. Conclusion: Advanced age and female gender are associated with site of denture impaction. Late hospital presentation significantly promotes sequelae associated with management of impacted dentures. It is recommended that fundamental changes in denture designs, education on regular follow-ups and avoidance of ill-fitting dentures would reduce the prevalence of denture impaction